River pollution and human health risks: Assessment in the locality areas proximity of Bengawan Solo river, Surakarta, Indonesia - Jean Baptiste Aboyitungiye; Suryanto; Evi Gravitiani (Research Centre of Inorganic Materials and Complexs, 2021)
Bengawan Solo River experiences a critical environment characterized by promiscuity and unsanitary on the part of its coasts. The locality inhabitants do not take the waste to appropriate places. This waste adorns streets, tributaries rivers and therefore ends up in the Bengawan Solo river during the rainy season. The discharge of waste in these various unconventional and unofficial places causes all kinds of nuisances, degrades the conditions of life and health of the population, and especially worsens the state of insalubrity of the river. In the light of the results obtained, waste constitutes mountains of garbage dumped in the sides of the river, the gutters, along the rails, and especially in illegal dumps and very often, in places of stagnation of water. It turned out that this waste has an impact on the health of populations. From the objective through qualitative analyzes to research subjects, this research gives recommendations and contributions on Indonesian waste management regulations towards health risks prevention of inhabitants surrounding the riverbanks.